Improving Learning Outcomes in the Use of Capital Letters Through Story Pictures for Grade Two Elementary Schools - Denni Juliarti (CV. Media Inti Teknologi, 2023)
The purpose of this study was to improve students' ability to use capital letters in writing short texts in class II of Elementary School 52 Bengkulu City. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles. The subjects in this study were class II students at SDN 52 Bengkulu City, namely 26 students consisting of 12 students and 14 female students. The object under study is the increase in the ability to use capital letters. Data collection techniques in the form of tests and non-tests. The research instrument uses a test to measure students' ability to use capital letters. Observation to assess the teaching and learning activities carried out. The results of the study in the first cycle showed that students' ability to use capital letters was still low. The results of the observation sheet on the implementation of lesson plans in cycle I obtained low results. The results of the study in cycle II the ability to use capital letters improved to be good. In cycle II the observation sheet for the implementation of lesson plans obtained good results. These results have reached the criteria of success. Thus, this research has been terminated.